PROMIS Peer Relationships Short Form: How Well Does Self-Report Correlate With Data From Peers?. (24th May 2018) - Devine, Katie A; Willard, Victoria W; Hocking, Matthew C; Stapleton, Jerod L; Rotter, David; Bukowski, William M; Noll, Robert B
Abstract: Objective: To examine the psychometric properties of the Patient-Reported Outcomes Measurement Information System (PROMIS ® ) peer relationships short form (PR-SF), including association with peer-reported friendships, likeability, and social reputation. Method: 203 children ( M age = 10.12 years, SD = 2.37, range = 6–14) in Grades 1–8 completed the 8-item PR-SF and friendship nominations, like ratings, and social reputation measures about their peers during 2 classroom visits approximately 4 months apart, as part of a larger study. A confirmatory factor analysis, followed by an exploratory factor analysis, was conducted to examine the factor structure of the PR-SF. Spearman correlations between the PR-SF and peer-reported outcomes evaluated construct validity. Results: For the PR-SF, a 2-factor solution demonstrated better fit than a 1-factor solution. The 2 factors appear to assess friendship quality (3 items) and peer acceptance (5 items). Reliability was marginal for the friendship quality factor (.66) but adequate for the acceptance factor (.85); stability was .34 for the PR-SF over 4 months. The PR-SF (8 items) and acceptance factor (5 items) both had modest but significant correlations with measures of friendship ( r s = .25–.27), likeability ( r s = .21–.22), and social reputation ( r s = .29–.44). Conclusions: The PR-SF appears to be measuring two distinct aspects of social functioning. The 5-item peer acceptance scale is modestly associated with peer-reported friendship, likeability, and social reputation. Although not a replacement for peer-reported outcomes, the PR-SF is a promising patient-reported outcome for peer relationships in youth.